Establishment of optimal mandibular incisor inclination: A retrospective comparison between surgery-first and conventional orthodontic approaches - Sang-Min Jeon; KyungMin Clara Lee (PLoS ONE, 2026)
Introduction Surgery-first orthodontic treatment offers early facial profile improvement and shorter treatment duration. This study investigated the incisor relationship in skeletal Class III malocclusion patients treated with conventional orthognathic surgery (COS) and the surgery-first approach (SFA). Materials and methods Sixty-eight patients who underwent mandibular setback surgery for skeletal Class III malocclusion were divided into 2 groups: the COS group (n = 34, 19 males and 15 females; mean age, 20.5 ± 2.9 years) treated with conventional three-stage surgical orthodontic treatment and the SFA group (n = 34, 20 males and 14 females; mean age, 21.9 ± 3.5 years) treated without presurgical orthodontics. Lateral cephalograms were analyzed before treatment (T0) and after debonding (T1). The changing pattern of mandibular incisor mandibular plane angle (IMPA) was compared between the groups, and the amount of change was assessed using analysis of covariance (ANCOVA) and mandibular incisor inclinations at each stage were compared to the norm value to calculate the achievement ratio. Results At T0, the IMPA was 81.6° in the COS group and 80.7° in the SFA group. At T1, the IMPA was 88.6° in the COS group and 83.3° in the SFA group. Considerable presurgical decompensation occurred in the COS group, while postsurgical decompensation was insufficient in the SFA group. ANCOVA revealed that the COS group exhibited a significantly greater change in IMPA than the SFA group (p = 0.001). At T1, the achievement ratio showed that the COS group (94.4%) was closer to the norm than the SFA group (85.5%) (p = 0.001), indicating that the SFA group showed more compensated mandibular incisors than the COS group. Conclusion The COS group demonstrated more effective mandibular incisor decompensation and achieved values closer to the norm than the SFA group. These findings suggest that presurgical orthodontics is essential for achieving optimal incisor inclination, and clinicians should carefully consider the need for sufficient decompensation when planning treatment with the SFA approach.